Technologies and innovation for improving performances logistic operators: the Techlog project - Gianfranco Fancello (International Business Logistics Journal)
Analyzing world maritime flows, the Mediterranean Sea is playing an increasingly central role in the world scenarios of goods transport and logistics: from 2006 to 2021 maritime traffic in the Mediterranean increased by 108% and today the Mediterranean area is involved in at least 12% of the worldwide maritime flows (Notteboom et al., 2019). in fact, the whole Med area has a strategic role related to its key positioning along the major East-West trading routes that linked all most important world freight markets (regarding Atlantic, European, Asian and African areas). About 40% of worldwide-containerized trade flows is handled by Mediterranean container ports and between 2010 and 2020, the total container volumes in Med area increased about 46% (UNCTAD, 2021). Despite this quick development, some elements threaten the primary role of the Mediterranean in the scenario of world maritime traffic flows: the artic route represents, alas due to global warming and climate change, a possible and increasingly capable route to significantly reduce the connection time between the Far East and Central Europe; the recent blockage of the Suez Canal has highlighted how it could become a real bottleneck for the development of the Mediterranean Sea, thus, stimulating the identification of new routes (Fancello et al. 2021).